Paradigm Shifts in Applied Linguistics: Its Impact on Research Methodology and Findings - Hasanah, Atiq Aqiqotul (Lumbung Pare Cendekia, 2024)
This article discusses the paradigm shift taking place in the field of applied linguistics and its impact on research methodology and discoveries. Along with the development of science and technology, paradigms in applied linguistics have undergone significant changes, especially in the way researchers approach linguistic problems and the methodologies used in their research. This paradigm shift includes changes in the understanding of language and communication, as well as the integration of linguistics with other disciplines such as computer science, psychology, anthropology, and neuroscience. This article will discuss how this shift has led to the development of more holistic and interdisciplinary research methodologies, allowing researchers to delve deeper into the complex aspects of language and human communication. In addition, this article will also explain how this paradigm shift has helped produce discoveries that enrich our understanding of language and communication, including its practical applications in areas such as information technology, machine translation, sentiment analysis, and machine learning. Paradigm shifts in applied linguistics are not only affecting the way we understand language but also how we harness it for innovation and advancement in various sectors. As such, this article will detail the paradigm shift in applied linguistics, highlight its impact on changes in research methodology, as well as describe the discoveries that have emerged as a result of these changes. A deeper understanding of this shift can help us design research more effectively and harness the potential of language and human communication in various aspects of modern life.